Poultry health constraints in smallholder village poultry systems in Northern Ghana and Central Tanzania - Ouma, Emily Awuor; Kankya, Clovice; Dione, Michel; Kelly, Terra; Enahoro, Dolapo; Chiwanga, Gaspar; Abukari, Yakubu; Msoffe, Peter; Kayang, Boniface Baboreka; Zhou, Huaijun (Frontiers in Veterinary Science, 2023)
Introduction Smallholder poultry production is a major contributor to food security and rural livelihoods in low-and middle-income countries. However, infectious diseases limit improvements to smallholder poultry production and performance of the sector in general. Infectious diseases of poultry, especially viral diseases, have major impacts on the health and productivity of flocks and account for significant morbidities and mortalities of birds each year. Methods This study utilized participatory epidemiology approaches to better understand the poultry health constraints and challenges faced by smallholder poultry producers in village poultry systems in Northern Ghana and Central Tanzania. Results The results show dominance of small-scale semi-intensive and extensive scavenging poultry production systems in the study areas. Newcastle disease ranked as the highest cause of morbidity and mortality in chickens in the two countries. The disease occurred mainly during the months coinciding with the dry season in both countries. Other health challenges among poultry flocks included worm infestation, fowl pox, coryza, and coccidiosis. Producers, especially in rural locations, had poor access to veterinary services and critical inputs necessary for poultry production. In the Northern region of Ghana, producers lacked definitive diagnoses for sick poultry due to a shortage of veterinary personnel and diagnostic laboratories. Discussion These challenges point to the need for increased investment in poultry disease control and prevention programs, particularly in rural areas. Interventions focused on expansion of veterinary and agricultural extension services and diagnostic laboratory capacity in rural areas and increased gender-sensitive training to enhance smallholder knowledge in poultry husbandry and disease prevention measures will support the development of the smallholder village poultry systems. Tapping into the diverse genetic reservoir of local chicken ecotypes with enhanced resistance to Newcastle disease through genomic selection, coupled with models for enhancing ND vaccination supply and use in the rural areas are potential future avenues for addressing ND constraints to production.